2006
DOI: 10.1128/jvi.00855-06
|View full text |Cite
|
Sign up to set email alerts
|

Role of Bim in Regulating CD8+T-Cell Responses during Chronic Viral Infection

Abstract: Apoptosis is critical for the development and maintenance of the immune system. The proapoptotic Bcl-2 family member Bim is important for normal immune system homeostasis. NP396-404؉ T cells in Bim mutant mice were due to lack of apoptosis and could not be explained by altered proliferation, differential homing to tissues, or increased help from CD4 ؉ T cells. When viral titers were examined, high levels were initially observed in both groups, but in Bim mutant mice, clearance from the spleen and sera was sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
56
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 50 publications
6
56
0
2
Order By: Relevance
“…However, this study has not investigated the roles of different APC types. Similarly, bim was found to delete immunodominant CTL responses in a murine model of chronic LCMV responses [41], explaining earlier reports of high dose antigenic deletion of LCMV-specific CTL [42].…”
Section: Discussionsupporting
confidence: 67%
“…However, this study has not investigated the roles of different APC types. Similarly, bim was found to delete immunodominant CTL responses in a murine model of chronic LCMV responses [41], explaining earlier reports of high dose antigenic deletion of LCMV-specific CTL [42].…”
Section: Discussionsupporting
confidence: 67%
“…Previous work by us and others showed that Bim was required for apoptotic contraction of superantigen-reactive and virus-specific T cells in vivo (12,14,20,27). We showed that following infection with lymphocytic choriomeningitis virus (LCMV), the absence of apoptotic contraction in Bim Ϫ/Ϫ mice resulted in significantly increased numbers of memory pheno- FIG.…”
Section: Discussionmentioning
confidence: 78%
“…This decision between death and survival is crucial for avoiding autoimmunity and for promoting the development of immunological memory and protective immunity. We and others have recently shown that Bcl-2 family members play a significant role in the apoptotic demise of activated effector T cells during acute and chronic viral infections (12,20,27). However, it remains unclear whether the failure to eliminate effector T cells can result in functionally increased protective immunity in vivo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Apoptosis of CD8 + T cells is controlled by the intrinsic (or mitochondrial) pathway, which is mediated by activation of the proapoptotic BH3-only proteins (e.g., Bcl-2-interacting mediator of death [Bim]), and the extrinsic pathway, which is mediated by ligation of death receptors (e.g., Fas or TNFR) (3,9). The Bimmediated intrinsic pathway controls both T cell contraction in acute infection and the persistence of Ag-specific CD8 + T cells in chronic infection (3,(10)(11)(12)(13)(14)(15). In acute infections, Fas/Fas ligand (FasL)-triggered cell death is dispensable for CD8 + T cell contraction (13,16); however, it could compensate for the loss of Bim in another infection model (14), and both Bim and Fas were shown to cooperate in controlling the cell death of Ag-stimulated CD8 + T cells in chronic infection (12,(17)(18)(19).…”
mentioning
confidence: 99%